Historical Memory of PKRI Veterans 1945-1949 (Rescuing Local Historical Sources in Banyuwangi): Historical memory Veteran PKRI tahun 1945-1949 (Penyelamatan Sumber Sejarah Lokal Banyuwangi) - miskawi; Ahmad Sulthoni (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Collective memory of a nation is the result of the process of identifying the memories of historical actors in the heroic events of the physical revolution of the Indonesian Independence fighters (PKRI) who were members of the Indonesian Veteran Legion (LVRI). The number of Independence Fighters is decreasing so that historical memory needs to be saved as a historical source through the excavation of oral history. The aim of this study is to reveal the historical memory of PKRI Veterans in 1945-1949 in an effort to save local historical sources. The method used is the historical method with oral history techniques. Informants are key actors in the revolutionary events of 1945-1949. The results of the study show that the historical actors of 1945-1949 were not from the armed forces but from the people who were members of the armed forces and paramilitaries recognized by the government. In general, it started from the awareness to defend independence by choosing guerrilla warfare. The army and the people fought to defend the country. Victory in war is determined by the strength of the people who are united. Historical Memory is presented in a contemporary context so that it can foster a spirit of nationalism, build historical awareness and can be used as a source of learning history.